PENGARUH GENERAL THERAPY HALUSINASI TERHADAP KEMAMPUAN MENGONTROL HALUSINASI PADA PASIEN SKIZOFRENIA DI WILAYAH KERJA PUSKESMAS KUMUN KOTA SUNGAI PENUH TAHUN 2022 - Del Fatma Wati; Fera Afri Santhi; Ratna Dewi (Universitas Fort De Kock, 2023)
ABSTRACTWHO stated that the incidence of schizophrenia in the world reached 20 million cases, while in the working area of the Kumun Health Center there were 22 cases of schizophrenia in 2020 and increased significantly to 50 cases in 2021. One type of disorder in schizophrenia patients is sensory perception (hallucinations). Hallucinations have fatal consequences such as acts of violence and suicide for the patient. This study aimed to determine the effect of hallucination general therapy on the ability to control hallucinations in schizophrenic patients in the working area of the Kumun Health Center in 2022. The type of this research was a quasy experiment with a one group pre test post test design approach which was carried out on October to November 2022. By using total sampling technique, 16 people were chosen as the samples. The data were collected through Keliat hallucination control instrument, et al (2019). Then, it was analyzed univariate and bivariate analysis by using paired t-test. The results showed that the average score of respondents' ability to control hallucinations before the intervention was 5.56 and after the intervention increased to 8. There was a difference in the average ability to control hallucinations between before and after giving general therapy with an average difference of 2.43 and the score p = 0.000. In short, it can be concluded that giving general therapy had a significant effect on increasing the ability to control hallucinations in schizophrenic patients. Therefore it is hoped that all parties, especially Kumun Community Health Center apply general therapy regularly and continuously in nursing care for schizophrenic patients with hallucinations.Keywords : General therapy, hallucinations, schizophreniaABSTRAKSecara global WHO menyatakan bahwa kejadian skizofrenia di dunia mencapai 20 juta kasus, sedangkan di wilayah kerja Puskesmas Kumun tercatat sebanyak 22 kasus skizofrenia di tahun 2020 dan meningkat signifikan menjadi 50 kasus di tahun 2021. Salah satu jenis gangguan pada pasien skizofrenia adalah persepsi sensori (halusinasi) yang dapat berakibat fatal seperti tindakan kekerasan dan bunuh diri bagi pasien. Penelitian ini bertujuan untuk mengetahui pengaruh general therapy halusinasi terhadap kemampuan mengontrol halusinasi pada pasien skizofrenia di wilayah kerja Puskesmas Kumun tahun 2022. Jenis penelitian ini adalah quasy experimen dengan pendekatan one group pre test post test design yang telah dilaksanakan pada bulan Oktober – November 2022. Jumlah sampel dalam penelitian ini sebanyak 16 orang. Pengambilan sampel menggunakan teknik total sampling. Pengumpulan data menggunakan instrumen pengendalian halusinasi Keliat, dkk (2019). Analisis data meliputi analisis univariat dan analisis bivariat menggunakan uji paired t-test. Hasil penelitian menunjukkan bahwa rata-rata skor kemampuan pengendalian halusinasi responden sebelum intervensi adalah 5,56 dan setelah intervensi meningkat menjadi 8. Terdapat perbedaan rata-rata kemampuan pengendalian halusinasi antara sebelum dan sesudah pemberian general therapy dengan beda rata-rata 2,43 dan nilai p = 0,000. Disimpulkan bahwa pemberian general therapy berpengaruh signifikan terhadap peningkatan kemampuan pengendalian halusinasi pada pasien skizofrenia. Maka dari itu diharapkan kepada semua pihak, terutama pihak Puskesmas Kumun untuk dapat menerapkan general therapy secara berkala dan berkesinambungan dalam asuhan keperawatan pada pasien skizofrenia dengan halusinasi.Kata Kunci : General therapy, halusinasi, skizofrenia